Perception of medical students towards serving rural people: A study from central India - Choudhary, Yachana; Dubey, Manju; Toppo, Manju; Pal, D. K. (International Journal Of Community Medicine And Public Health, 2018)
Background: India is facing critical problem of paucity of certified physicians in rural areas, although majority of the population resides in rural areas. According to rural health statistics report 2015, there is a deficit of 659 doctors in rural areas. The study was done with the objective to capture the perception among medical students (interns / postgraduates) about their preference of work place after graduation/post-graduation and to know the factors responsible for preference / non-preference. Methods: A cross sectional study was carried out, among 203 medical students in a government medical college of Bhopal (M.P) from January to March 2016. A semi-structured questionnaire was used to obtain information regarding their preference to serve in rural areas and reasons associated with their choices. The data was entered in MS excel and analysis was performed using Epi-Info7. Results: The study participants included 203 medical students, only 33 (16.26%), were willing to work in rural area. The major reasons for non-preference of rural area were lack of primary facilities like equipments, paramedical staff, non favorable working conditions. Majority of them responded that good salary, better lifestyle and security for doctors especially for females would make them work there. Conclusions: Very less proportion of study participants preferred rural area as their preferred work place. Our study has shown a need for intervention to overcome these perceptions and attitudes of the students towards practice in rural area in order to reverse this disparity.